Fave 2 Face Intermediate. Workbook - Tims, Nicholas and Redston, Chris (Cambridge Cambridge University Press, 2007)
Face 2 Face is a general English course for adults and young adults who want to learn to communicate quickly and effectively in todays world. Based on the communicative approach, it combines the best in current methodology with special new features designed to make learning and teaching easier. Vocabulary and grammar are given equal importance and there is a strong focus on listening and speaking in social situations.
Keywords: English Practice